2002
DOI: 10.1037/0021-9010.87.4.735
|View full text |Cite
|
Sign up to set email alerts
|

A new frame for frame-of-reference training: Enhancing the construct validity of assessment centers.

Abstract: The authors undertook a comprehensive examination of the construct validity of an assessment center in this study by (a) gathering many different types of evidence to evaluate the strength of the inference between predictor measures and constructs (e.g., reliability, accuracy, convergent and discriminant relationships), (b) introducing a theoretically relevant intervention (frame-of-reference [FOR] training) aimed at improving construct validity, and (c) examining the effect of this intervention on criterion-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
108
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(115 citation statements)
references
References 69 publications
4
108
3
Order By: Relevance
“…The general framework of validity (Binning & Barrett, 1989;Schleicher et al, 2002) suggested that transparency improved interviews' criterion-related validity due to a reduction of error. Conversely, Kleinmann's (1993) idea of a stable ability to identify the requirements or social situations suggested that transparency would suppress an ability that otherwise contributed to the procedure's criterion-related validity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The general framework of validity (Binning & Barrett, 1989;Schleicher et al, 2002) suggested that transparency improved interviews' criterion-related validity due to a reduction of error. Conversely, Kleinmann's (1993) idea of a stable ability to identify the requirements or social situations suggested that transparency would suppress an ability that otherwise contributed to the procedure's criterion-related validity.…”
Section: Discussionmentioning
confidence: 99%
“…For personnel selection, however, an interview's criterion-related validity is of primary concern. The general framework of validity (Binning & Barrett, 1989;Cascio, 1998;Schleicher, Day, Mayes, & Riggio, 2002) suggests that interviews' criterion-related validity should improve with interview transparency. If interviewees' erroneous interpretations in nontransparent interviews distract them from answering in line with the required dimensions, this will introduce error into the measurement of those applicant characteristics that had been identified as relevant in the job analysis.…”
Section: Consequences Of Interview Transparency On Criterion-related mentioning
confidence: 99%
“…In particular, frame-of-reference (FOR) training is one possible approach for improving rater reliability and accuracy (London et al 2004;Schleicher et al 2002). FOR training changes the impression formation process of raters to more trait-based (as opposed to behavioral-based) representations of the ratee (Schleicher et al 2002).…”
Section: Implications and Future Research Directionsmentioning
confidence: 99%
“…The logical expectation is that the correlations within the competencies and between the exercises would be greater than the correlations within the exercises and between the competencies; however, the opposite is commonly found (Woodruffe, 2000) and this is true of the current data. Remedies, typically in the form of improvements in assessor training including increasing the length of assessor training, limiting competencies, and listing key behaviours have been suggested (Lievens, 2002;Schleicher, Day, Mayes and Riggio, 2002). These strategies have been found to reduce exercise effects (Lievens, 2002;Schleicher, et al, 2002); however, most of these were utilised in the present design.…”
Section: Discussionmentioning
confidence: 75%
“…Remedies, typically in the form of improvements in assessor training including increasing the length of assessor training, limiting competencies, and listing key behaviours have been suggested (Lievens, 2002;Schleicher, Day, Mayes and Riggio, 2002). These strategies have been found to reduce exercise effects (Lievens, 2002;Schleicher, et al, 2002); however, most of these were utilised in the present design. Nevertheless, improvements are planned for assessor training.…”
Section: Discussionmentioning
confidence: 75%